High-grade well-differentiated neuroendocrine tumour of the cecum diagnosed following incisional hernia repair: a case report - Juškys, Raimondas; Poškus, Eligijus; Beiša, Augustas; Gumbys, Liutauras; Jocius, Donatas; Meškauskas, Raimundas; Strupas, Kęstutis (Acta medica Lituanica, 2020)
High-grade well-differentiated neuroendocrine tumour tumours (NETs) of gastrointestinal tract are rare; they can arise in any part of the digestive system and usually present in advanced stages. Low incidence and wide heterogeneity in the biological behaviour of such lesions pose a diagnostic and therapeutic challenge. Loco-regional NETs should be resected whenever feasible, potentially with a curative intent. Management of a metastatic disease is often more complex, primarily aimed at the alleviation of symptoms, prevention of further complications, and prolongation of survival. Current literature describing the optimal treatment plan for such patients is sparse and further studies are necessary to enhance our understanding of the disease. Here we present a case of high-grade well-differentiated cecal NET with an associated carcinoid syndrome that was diagnosed following the incisional hernia repair.